Theories of Disease Causation: An Overview - Dharmashree Satyarup1, Manish Kumar2, Radha Prasanna Dalai3, Sharmistha Mohanty4, Karishma R. Rathor (Indian Journal of Forensic Medicine & Toxicology, 2020)
Disease is an important entity in healthcare. In-depth understanding of disease causation aids in planningprevention and steps to tackle the disease in a population. The outlook regarding disease causation haschanged considerably with time and advancements in science. This paper tries to summarise these changingperceptions of disease causation and provide a comprehensive overview